Lauroyl Arginate Ethyl Blocks the Iron Signals Necessary for Pseudomonas aeruginosa Biofilm Development - Kim, Taek-Seung; Ham, So-Young; Park, Bernie B.; Byun, Youngjoo; Park, Hee-Deung (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is a ubiquitous gram-negative bacterium capable of forming a biofilm on living and non-living surfaces, which frequently leads to undesirable consequences. We found that lauroyl arginate ethyl (LAE), a synthetic non-oxidizing biocide, inhibited biofilm formation by P. aeruginosa at a sub-growth inhibitory concentration under both static and flow conditions. A global transcriptome analysis was conducted using a gene chip microarray to identify the genes targeted by LAE. In response to LAE treatment, P. aeruginosa cells up-regulated iron acquisition and signaling genes and down-regulated iron storage genes. LAE demonstrated the capacity to chelate iron in an experiment in which free LAE molecules were measured by increasing the ratio of iron to LAE. Furthermore, compared to untreated cells, P. aeruginosa cells treated with LAE exhibited enhanced twitching motility, a phenotype that is usually evident when the cells are starved for iron. Taken together, these results imply that LAE generated iron-limiting conditions, and in turn, blocked iron signals necessary for P. aeruginosa biofilm development. As destroying or blocking signals leading to biofilm development would be an efficient way to mitigate problematic biofilms, our findings suggest that LAE can aid in reducing P. aeruginosa biofilms for therapeutic and industrial purposes.